The assessment of the thermal behavior of an urban park surface in a dense urban area for planning decisions - Adiguzel, Fatih; Cetin, Mehmet; Dogan, Mesut; Gungor, Senay; Kose, Mustafa; Bozdogan Sert, Elif; Kaya, Efdal (Springer Science and Business Media LLC, 2022)
The new summer index (SSI) which was established to determine climate comfort was classified according to the index. Climatic comfort areas will increase and thus raising the quality of living in areas. The temperature values felt in the study were calculated with the SSI formula, and then the maps of the study area were classified. The study area was the Hayal Park and its surroundings in the Toros Quarter of Cukurova District, which is surrounded by multi-story and dense buildings in the north of Adana. Although the vertical construction is very high, it is richer in terms of green areas compared to other large central districts. Cukurova, which is one of the largest districts of Adana (according to population), has Seyhan dam lake in the north and Seyhan district in the south. The study area is on the border of Seyhan district and is adjacent to Yüreğir and Sarıçam districts. With the portable Smart SENSOR AS 847 measuring device, temperature and relative humidity were measured at 1.5 m above the ground on Tuesday, August 20 at 07.00, at 14.00, and 21.00. Bioclimatic comfort areas were determined by measuring temperature and relative humidity at 25 points with different textures in the study area. In this study, measured instantaneous temperature (°C) and relative humidity (%) data were transferred to GIS medium by ArcGIS 10.6 program and then modeled with the Kriging method, which is one of the interpolation methods, and temperature and relative humidity maps were created. The temperature map created in degrees Celsius (°C) by the Kriging method and was converted to Fahrenheit degrees (°F) in the Raster Calculator. The reason for this change is that SSI is calculated with the formula Fahrenheit (°F). These maps were then calculated on the Raster Calculator using the SSI formula, and sensed temperature values were obtained The SSI, which normally has 8 classes, has 3 classes in the study area. These classes are 83 ≤ SSI < 91 slightly hot, 91 ≤ SSI < 100 hot, and 100 ≤ SSI < 112 very hot. When we look at the maps, the places outside of Hayal Park are in the hot class at 07.00 in the morning, and we can see that the green spaces have a positive effect on the bioclimatic comfort areas. The small area is in a very hot class. When we look at 14.00 h, it is a totally hot class. Normally, the temperature is the highest of these times and also coincides with the multi-story buildings in the study area; asphalt and concrete areas increased the temperature. As a result, there is a very hot air in the study area. It was determined that the maps identified non-comfortable areas. Since urban form and settlement affect climate comfort values, the urban plan should be revised, and the area should be brought to the bioclimatic comfort value range. For reducing the effect of temperature in the working area and creating comfortable areas is increasing the density of green areas compared to asphalt and concrete areas. Considering that the Cukurova district will grow further, urban planning should be done very well to reach the comfort range in the following settlements.
Keywords: Hot Temperature; Parks; Mathematical computing; Climate; Parks, Recreational; Hot temperature; Thermal comfort; Turkey (republic); Atmospheric temperature; Skis; Urban planning; Information; building; City Planning; Island (geological); Data Collection; Surface property; Temperature; Environmental monitoring; Textures; Dam (barrier); GIS; Cukurovum district; Kriging; Impact; Recreational; Data collection; Temperature values; Classifieds; Geographic information system; Study areas; Environmental Monitoring; Rasterization; Summer; Summer index; Urban heat island; Snow Making; Environmental Sciences & Ecology; Climate comfort; Skiing; Cities; Thermal comfort zone; Climate-change; Tourism climate; Weather; Environmental temperature; City planning; Temperature measurement; Green areas; Temperature and relative humidity; Lake ecosystem; Cukurova district; Zoning; Relative humidity; Urban area; Political instability; Comfort; Environmental factor; Index; Interpolation; Agriculture, Environment & Ecology - Forestry - Syntaxonomy; Decision making; Temperature sensitivity; 11. Sustainability; 13. Climate action